Calculation Of Magnetic Circuits With A Moving Screen Using The Superimposition Method - Boltaev Otabek Tashmukhammatovich; Akhmedova Firuza Anvarovna (Genius Journals, 2025)
The article considers the sequence of calculations using the method of superimposing magnetic circuits with a movable electromagnetic screen and when the parameters of the magnetic circuit are determined using different methods, the difference between the results is 1÷3%, and the difference between the theoretical and experimental results is found to be no more than 4÷7%.
Keywords: movable screen; magnetic circuit; compensating device